1996
DOI: 10.1074/jbc.271.36.22130
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Amino Acid Sequence of a New 22-kDa FKBP-like Peptidyl-prolyl cis/trans-Isomerase of Escherichia coli

Abstract: We identified a periplasmic peptidyl-prolyl cis/transisomerase (PPIase) of the (FK506-binding protein (FKBP) type in Escherichia coli (FK506 represents a natural peptidomacrolide containing an acylated pipecolic acid residue). After purification to homogeneity, its complete amino acid sequence was determined by a combination of Edman degradation and electrospray mass spectrometry of the authentic protein and peptides generated by proteolysis. The molecular mass calculated from the amino acid sequence of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 46 publications
5
56
0
4
Order By: Relevance
“…However, at least one of these putative gene products most likely plays a role in protein folding. LptB shows strong homology to FKBP-like peptidylprolyl cis/trans isomerases, which catalyze the interconversion of the proline peptide bonds between the cis and trans isomers (46). This proposed function of LptB is in keeping with the nature of the majority of genes controlled by AlgU (i.e., stress response or protein folding) identified here and elsewhere (14,18,32,38).…”
Section: Discussionsupporting
confidence: 56%
“…However, at least one of these putative gene products most likely plays a role in protein folding. LptB shows strong homology to FKBP-like peptidylprolyl cis/trans isomerases, which catalyze the interconversion of the proline peptide bonds between the cis and trans isomers (46). This proposed function of LptB is in keeping with the nature of the majority of genes controlled by AlgU (i.e., stress response or protein folding) identified here and elsewhere (14,18,32,38).…”
Section: Discussionsupporting
confidence: 56%
“…Below Hsa12 are the sequences for the homologues of FKBP12 in the eukaryotes N. crassa (Ncr16) and S. cerevisiae (Sce11). The three sequences below the eukaryotic sequences are Mip sequences: the Mip protein of L. pneumoniae (LpMip) and the Mip-like sequences of E. coli [EcMip1, also known as FkpA (Horne and Young, 1995), and EcMip2, also known as FklB (Rahfeld et al, 1996)]. The bottom sequence is the E. coli trigger factor (EcTig).…”
Section: Modelling Slyd On the Fkbp12 Structurementioning
confidence: 99%
“…The tig gene, at 9.8 min, encodes the 'trigger factor', which was originally thought to be involved in protein secretion (Crooke and Wickner, 1987) but more recently has been identified as an abundant FKBP-type PPIase associated with ribosomes and nascent peptides (Stoller et al, 1995;Hesterkamp and Bukau, 1996). Two Mip-like FKBP PPIases have been identified, one encoded by fkpA at 74.9 min (Horne and Young, 1995) and the other by fklB at 95.4 min (Rahfeld et al, 1996). slpA (formerly orf149) is part of the lspA operon at 0.6 min and encodes a cytosolic PPIase of unknown function (Bouvier and Stragier, 1991;Hottenrott et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking experiments with dimethyl pimelimidate (DMP) revealed that Legionella Mip forms homodimers both in solution and on the bacterial surface (43,44). In this respect the Legionella protein resembles FKBP22 and FkpA from E. coli, which were also shown to form dimers in solution (35,36). More recently, the 2.4-Å crystal structure of the Mip protein from L. pneumophila Philadelphia 1 was determined (39).…”
mentioning
confidence: 99%